Use of the Hedgehog signaling pathway inhibitor in the treatment of recurrent locally advanced and metastatic basal cell skin cancer - Z. A.-G. Radzhabova; M. A. Kotov; Z. S. Bekyasheva; M. A. Radzhabova; E. V. Levchenko (Опухоли головы и шеи)
The study objective is to provide data on the use of the Hedgehog signaling pathway inhibitor (vismodegib) in the treatment of recurrent locally advanced and metastatic basal cell skin cancer at the N. N. Petrov National Medical Research Center of Oncology.Materials and methods. Clinical data of 10 patients who participated in a multicenter, non-randomized clinical trial of phase II ERIVANCE BBC (ClinicalTrials. gov NCT833417). Patients took the daily studied drug vismodegib orally at a dose of 150 mg daily until disease progression or intolerance due to side effects. Efficiency and safety assessment was carried out once every 4 weeks.Results. Complete regression was achieved in 7 patients, while the average duration of use of the drug was 240 ± 65 days. Stabilization was observed in 2 patients, the minimum duration of the drug was 336 days. One patient showed progression after 728 days of taking the drug. Side effects of the 1 grade according to CTCAE (Common Terminology Criteria for Adverse Events), v. 3.0 were observed in all patients, in 9 they were expressed in muscle cramps, alopecia and changes in taste sensitivity, and in 1 patient isolated in the form of muscle cramps.Conclusion. The results show a good safety profile of vismodegib, which allows it to be used in elderly patients with concomitant pathology. The frequency of response to treatment, including the achievement of complete regression in 70 % of patients, makes vismodegib an acceptable treatment option for metastatic form of basal cell skin cancer and relapse of locally advanced forms.